Several FDA-Approved Drugs Effectively Inhibit SARS-CoV-2 Infection in vitro - Xiong, Hua-Long; Cao, Jia-Li; Shen, Chen-Guang; Ma, Jian; Qiao, Xiao-Yang; Shi, Tian-Shu; Ge, Sheng-Xiang; Ye, Hui-Ming; Zhang, Jun; Yuan, Quan; Zhang, Tian-Ying; Xia, Ning-Shao (Frontiers in Pharmacology, 2021)
To identify drugs that are potentially used for the treatment of COVID-19, the potency of 1403 FDA-approved drugs were evaluated using a robust pseudovirus assay and the candidates were further confirmed by authentic SARS-CoV-2 assay. Four compounds, Clomiphene (citrate), Vortioxetine, Vortioxetine (hydrobromide) and Asenapine (hydrochloride), showed potent inhibitory effects in both pseudovirus and authentic virus assay. The combination of Clomiphene (citrate), Vortioxetine and Asenapine (hydrochloride) is much more potent than used alone, with IC50 of 0.34 μM.